Optimization of pre-treated oil palm frond producing bioethanol via fermentation with Escherichia coli KO11: article - Roslan, Nur Aini; Azizan, Amizon; Darim, Rosmaria (2016)
Bioethanol production has been the great interest of worldwide due to intensive demand for the depleting fossil oil. The bioethanol as a fossil fuel substitute has drawn much attention as an alternative transportation fuel. Thus, the need for an alternative fuel from renewable resources contributes the sustainability that possibly to replace our dependence on fossil fuel. In this study, in order to investigate the high possibility of yield efficiency of bioethanol production will be mark on pre-treatment parameters. Ionic liquid (IL) pre-treatment has shown great potential as a novel pre-treatment technology with high sugar yields. To improve process economics of pre-treatment, higher biomass loading is desirable. It is an economical bioprocess to produce the fermentable sugars at laboratory scales Using Oil Palm Frond (OPF) as substrate in Simultaneous Saccharification and Fermentation (SSF). The high content of cellulose in OPF promises the high sugars production in SSF process. The simultaneous saccharification and fermentation (SSF) of oil palm frond waste by Escherichia coli (E.Coli) KO11generates fermentable sugars and was evaluated through this SSF. The tolerance of bacteria used will be analyse in SSF through oxygen uptake rate (OUR) and carbon dioxide evolution rate (CER). The oil palm frond (OPF) pre-treat has been carried out using 1-ethyl-3-methylimidazolium acetate [EMIM][Ac] with different concentration content. This is because the use of ionic liquid in the pre-treatment will be analyse as the concentration of the ionic liquid used is lower than 60% until the concentration reach to 20%. The analysis of using from intermediate to low concentration of ionic liquid in the high production of bioethanol and the gas chromatography – flame ionization detector for bioethanol composition will be investigate.